Facile synthesis and properties of the chemo-reversible and highly tunable metallogels based on polydicyclopentadiene. (16th June 2017) - Yao, Zhen; Wang, Zufei; Yu, Yunfei; Zeng, Changchun; Cao, Kun
Abstract: We report our study on the facile synthesis of reversible metallogels (metal coordinated polymer network) with tunable crosslinking density and metal ions, and the properties of the metallogels. The metallogels were prepared via non-covalent metal coordination crosslinking of functionalized soluble polydicyclopentadiene (sPDCPD). sPDCPD was first synthesized by ring-opening metathesis polymerization (ROMP) and functionalized using 3, 6-di-2- pyridinyl-1, 2, 4, 5-tetrazine (DPTZ) via the inverse electron-demand Diels-Alder (iEDDA) reaction. The structures of the synthesized macromolecular ligands DPTZ-sPDCPD were characterized by size-exclusion chromatography (SEC), Fourier transfer infrared spectroscopy (FITR) and nuclear magnetic resonance (NMR). Subsequently, DPTZ-sPDCPD was crosslinked by adding metal ions, e.g., Zinc or Nickel salts. Using the series of metallogels prepared, we investigated the effects of crosslinking densities, metal ion types, solvent types and polymer concentrations on the rheological properties of the prepared metallogels. We also demonstrated the excellent reversibility of the metallogel via repeated reclamation of the macromolecular ligands and metal coordination. Graphical abstract: Highlights: Chemo-reversible PDCPD-based metallogels with tunable crosslinking density were synthesized. The rheological properties of the prepared metallogels were investigated. The metallogels show excellent reversibility and reusability.